Philosophy of religion and two types of atheology - Shook, John R. (International journal of philosophy and theology, 2015)
Atheism is skeptical towards gods, and atheology advances philosophical positions defending the reasonableness of that rejection. The history of philosophy encompasses many unorthodox and irreligious movements of thought, and these varieties of unbelief deserve more exegesis and analysis than presently available. Going back to philosophy’s origins, two primary types of atheology have dominated the advancement of atheism, yet they have not cooperated very well. Materialist philosophies assemble cosmologies that leave nothing for gods to do, while skeptical philosophies find conceptions of god to be too unintelligible or unsupported by evidence to warrant credibility. The origins and genealogies of these two atheologies are sketched and compared over many centuries down to present-day atheism, which still displays signs of this internecine divide between confident naturalists and agnostic skeptics.